2022
DOI: 10.3390/ma15228154
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Quality Optimization Taguchi Design with Grey Relational Analysis of Halloysite Nanotube Hybrid Composite: CNC Machine Manufacturing

Abstract: Researchers who work on manufacturing hybrid composites have significant concerns about holistically optimizing more than one performance characteristic, as in the case of cost and quality optimization. They usually trade off one for the other. Hence, this study employed statistical tools and grey relational analyses (GRA) design to model and optimize the surface roughness and cutting force of Computer Numerical Control (CNC) machine settings to manufacture halloysite nanotube hybrid composite. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Figure 16 shows the fatigue test results of the RFW of ABS and PC dissimilar rods under five different rotational speeds. The results showed that the average number of cycles until rupture of the RFW of ABS and PC using a rotational speed of 330 rpm, 490 rpm, 650 rpm, 950 rpm, and 1350 rpm was about 35,150,39,120,42,145,48,957, and 53,240, respectively. It was found that the fatigue life of the RFW of ABS and PC increased with the increase in the rotational speed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 16 shows the fatigue test results of the RFW of ABS and PC dissimilar rods under five different rotational speeds. The results showed that the average number of cycles until rupture of the RFW of ABS and PC using a rotational speed of 330 rpm, 490 rpm, 650 rpm, 950 rpm, and 1350 rpm was about 35,150,39,120,42,145,48,957, and 53,240, respectively. It was found that the fatigue life of the RFW of ABS and PC increased with the increase in the rotational speed.…”
Section: Resultsmentioning
confidence: 99%
“…However, a lathe was used for the RFW in the current work. To reduce experimental error, the computer numerical control turning machine [ 42 , 43 , 44 , 45 ] was recommended to perform the RFW because the feed rate of RFW can be controlled precisely. In addition, the rotational speed [ 46 ] can be changed during the process of RFW.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a conventional turning machine was used to carry out the RFW of polymer rods. In future studies, a high-speed lathe or computer numerical control lathe [40,41] are recommended to carry out RFW [42][43][44][45]. These topics are currently being investigated, and the results will be presented in future work.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal settings were confirmed using the TOPSIS and MARCOS methods. Esangbedo et al [51] combined Taguchi design with grey relational analysis to optimize the cost and quality of a nanotube composite used in computer numerical control machines.…”
Section: Merec With Related Mcdm Methodsmentioning
confidence: 99%